World Science Forum: Trust in science and the sustainability challenges - Leonid Melnyk; Oleksandr Kubatko; Vladyslav Piven (Knowledge & Performance Management)
Type of the article: Editorial Acknowledgments The paper is prepared within the scientific research projects “Digital transformations to ensure civil protection and post-war economic recovery in the face of environmental and social challenges” (No. 0124U000549) and “Fundamental grounds for Ukraine’s transition to a digital economy based on the implementation of Industries 3.0; 4.0; 5.0” (No. 0124U000576).